Determination of ultra-trace metal-protein interactions in co-formulated monoclonal antibody drug product by SEC-ICP-MS - Laurence Whitty-Léveillé; Zachary L. VanAernum; Jorge Alexander Pavon; Christa Murphy; Katie Neal; William Forest; Xinliu Gao; Wendy Zhong; Douglas D. Richardson; Hillary A. Schuessler (Taylor & Francis Group, 2023)
ABSTRACTTransition metals can be introduced in therapeutic protein drugs at various steps of the manufacturing process (e.g. manufacturing raw materials, formulation, storage), and can cause a variety of modifications on the protein. These modifications can potentially influence the efficacy, safety, and stability of the therapeutic protein, especially if critical quality attributes (CQAs) are affected. Therefore, it is meaningful to understand the interactions between proteins and metals that can occur during the manufacturing process, formulation, and storage of biotherapeutics. Here, we describe a novel strategy to differentiate between ultra-trace levels of transition metals (cobalt, chromium, copper, iron, and nickel) interacting with therapeutic proteins and free metal in solution in the drug formulation using size exclusion chromatography coupled to inductively coupled plasma mass spectrometry (SEC-ICP-MS). Two monoclonal antibodies (mAbs) were coformulated and stored up to nine days in a scaled down model to mimic metal exposure from manufacturing tanks. The samples containing the mAbs were first analyzed by ICP-MS for bulk metal analysis, then studied using SEC-ICP-MS to measure the extent of metal-protein interactions. The SEC separation was used to differentiate metal associated with the mAbs from free metal in solution. Relative quantitation of metal-protein interaction was then calculated using the relative peak areas of protein-associated metal to free metal in solution and weighting it to the total metal concentration in the mixture as measured by bulk metal analysis by ICP-MS. The SEC-ICP-MS method offers an informative means of measuring metal-protein interactions during drug development.